The Influence of Product Quality, Brand Image and Promotion on The Purchase Decision of 3second Fashion - Rindi Rindi; Dr. Sengguruh Nilowardono; Agus Sukoco; Iga Aju Nitya Dharmani; Joko Suyono (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the effect of product quality, brand image and promotion on purchasing decisions of 3second Fashion Royal Plaza Surabaya fashion. A quantitative approach is used to answer the problems in this study, using 100 respondents. The analysis technique used is multiple linear regression analysis. The results show that, 1) Product quality influences purchasing decisions for the 3second Fashion Royal Plaza Surabaya fashion so that H1 is accepted. That is, the better the quality of the products sold, the higher the decision to buy the product. 2) Brand image influences purchasing decisions for 3second Fashion Royal Plaza Surabaya fashion so that H2 is accepted. That is, the better the brand image that is embedded in the minds of consumers, the decision to buy a product is increasing. 3) Promotion has an effect on purchasing decisions for 3second Fashion Royal Plaza Surabaya fashion so that H3 is accepted. That is, the more maximum promotional efforts made by the company, the decision to buy the product will increase. and 4) Product quality, brand image and promotion influence the purchasing decision of the 3second Fashion Royal Plaza Surabaya fashion so that H4 is accepted. That is, the existence of products with high quality, good brand image and maximum and well-targeted promotions will have an impact on increasing consumer purchasing decisions.